2021
DOI: 10.1038/s43856-021-00034-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced subgenomic RNA expression is a molecular indicator of asymptomatic SARS-CoV-2 infection

Abstract: Background It is estimated that up to 80% of infections caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are asymptomatic and asymptomatic patients can still effectively transmit the virus and cause disease. While much of the effort has been placed on decoding single nucleotide variation in SARS-CoV-2 genomes, considerably less is known about their transcript variation and any correlation with clinical severity in human hosts, as defined here by the presence or absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Instead, a significantly higher level of sgRNA was identified in patients with mild disease. This is an interesting finding as it has been reported that sgRNA transcripts are reduced in asymptomatic cases of COVID-19 ( Wong et al, 2021 ). However, this may be a result of the lack of intervention in mild cases compared to interventions which would have been received by hospitalised severe disease cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Instead, a significantly higher level of sgRNA was identified in patients with mild disease. This is an interesting finding as it has been reported that sgRNA transcripts are reduced in asymptomatic cases of COVID-19 ( Wong et al, 2021 ). However, this may be a result of the lack of intervention in mild cases compared to interventions which would have been received by hospitalised severe disease cases.…”
Section: Discussionsupporting
confidence: 71%
“…It is not well understood role sgRNA expression plays during infections. There have been reports that the detection of sgRNAs in clinical samples indicates an active viral infection, and expression levels correlate strongly to the severity of symptoms ( Wong et al, 2021 ). However, others report that sgRNA expression is not a reliable indicator of viral replication ( Alexandersen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional tests for interference behavior have yet to be performed to provide evidence that these variants are DIPs. In the case of SARS-CoV-2, genomes that harbor large identical deletions were found in multiple patients who had only mild symptoms or were asymptomatic [127,128]. It remains to be seen what role, if any, DVGs may play in the severity of COVID-19.…”
Section: Dips In Vivomentioning
confidence: 99%
“…No reports have been identified for the role of DVGs in IFN responses and viral persistence for SARS-CoV-2 infection so far. Interestingly, a COVID-19 cohort study (Wong, Ngan et al 2021) indicates that the abundance of TRS-independent deletions (>20nts) is significantly more in symptomatic patients than that in asymptomatic patients, suggesting a potential role of DVGs in modulating host responses and symptom development in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%